2023
DOI: 10.3390/pharmaceutics15010183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Penetration Enhancers on Transdermal Delivery of Oxcarbazepine, an Antiepileptic Drug Using Microemulsions

Abstract: Oxcarbazepine (OXC) is an anticonvulsant drug, indicated for the treatment of the neurological disorder, epilepsy. The objective of the present study was to evaluate the transdermal delivery of OXC from microemulsions using different penetration enhancers. Transcutol® P (TRC), oleic acid (OA), cineole (cin), Labrasol (LS), Tween 80 (T80) and N-Methyl-Pyrrolidone (NMP) were used as penetration enhancers as well as microemulsion components. Simple formulations of OXC in propylene glycol (PG) incorporating variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 50 publications
0
12
0
3
Order By: Relevance
“…In combination with Transcutol, the highest drug release was observed in our in vitro experiment, which can be explained by the synergistic penetration enhancer effect of the two excipients. Transcutol is often used in combination with other penetration enhancers; Amitkumar et al found that oleic acid and Transcutol in combination significantly improved the transdermal drug delivery of oxcarbazepine [ 49 ]. The dissolution from the patches without penetration enhancers was well described with the Weibull model.…”
Section: Discussionmentioning
confidence: 99%
“…In combination with Transcutol, the highest drug release was observed in our in vitro experiment, which can be explained by the synergistic penetration enhancer effect of the two excipients. Transcutol is often used in combination with other penetration enhancers; Amitkumar et al found that oleic acid and Transcutol in combination significantly improved the transdermal drug delivery of oxcarbazepine [ 49 ]. The dissolution from the patches without penetration enhancers was well described with the Weibull model.…”
Section: Discussionmentioning
confidence: 99%
“…Synergistic effects can be achieved when using certain combinations of penetration enhancers. There are many techniques used to exploit the synergistic behaviour of various penetration enhancers, such as co-solvency; creating eutectic mixtures; using vesicles such as liposomes, transfersomes and niosomes; and creating MEs [71,72]. PG, one of the most commonly used penetration-enhancing agents, is synergistic when combined with terpenes, OA, Azone ® , and IPM [12,63].…”
Section: Synergismmentioning
confidence: 99%
“…Ethanol has demonstrated synergistic behaviour when used with linoleic acid for the TD of lidocaine [73]. A combination of 5% OA and 5% DGME (Transcutol ® P) was able to synergistically enhance the transdermal flux of oxcarbazepine through human skin compared to OA or DGME alone [72]. Synergism has also been demonstrated when CPEs are used in combination with physical penetration-enhancing methods [74], such as iontophoresis [63,[75][76][77], sonophoresis [78], and electroporation [79].…”
Section: Synergismmentioning
confidence: 99%
“…After the assembled FDCs were allowed to equilibrate for a minimum of 30 min, 500 µL of each formulation was applied to the skin in the donor compartment as described by Virani et al [35,36]. At specific time intervals, a 300 µL sample of the receptor medium was withdrawn, and an equivalent volume of fresh buffer solution was added to the receptor chamber.…”
Section: In Vitro Skin Permeation Studymentioning
confidence: 99%